Lack of Sex Differences to the Subjective Effects of Nitrous Oxide in Healthy Volunteers - Zacny, James P. (2010)
BACKGROUND: Although numerous studies have assessed subjective effects of nitrous oxide, few studies have analyzed for sex differences. Since sex differences have been reported in subjective effects of several drugs such as opioids, nicotine and alcohol, we sought to determine if sex modulates the subjective effects of the inhalant, nitrous oxide, in healthy volunteers. METHODS: Thirty-eight females and seventy-two males from nine studies that were conducted in our laboratory were included in this retrospective analysis. All experimental studies utilized randomized, placebo controlled, repeated measures designs in which subjects inhaled 30% nitrous oxide in oxygen and 100% oxygen (placebo). Dependent measures in this analysis were subjective effects measured at baseline and 15 min into the inhalation period. RESULTS: Nitrous oxide produced a number of subjective effects, including those that could be considered abuse liability-related (“elated,” “having pleasant thoughts,” drug liking), but sex did not modulate these effects. CONCLUSIONS: Females and males showed similar subjective responses to 30% nitrous oxide. Future prospective studies might assess other concentrations, other measures (choice, analgesic response), and other inhaled general anesthetics to more comprehensively characterize the role of sex in response to inhalants.